Laser Powder Bed Fusion 공정으로 적층 제조된 Inconel 718 합금 격자 구조체의 압축 변형 거동에 미치는 격자 크기의 영향 - 강태훈; Tae-hoon Kang; Holden Hyer; Yongho Sohn; 이기안; Kee-ahn Lee (대한금속·재료학회지, 63(11), 2025)
This study investigates the mechanical behavior and deformation characteristics of Inconel 718 lattice structures with different unit cell sizes fabricated by laser powder bed fusion (LPBF). Two bodycentered cubic (BCC) lattice structures with unit cell sizes of 2 mm (BCC 2) and 4 mm (BCC 4) were designed while maintaining a constant strut diameter. The measured relative densities were 31.48% for BCC 2 and 8.67% for BCC 4, indicating a significant reduction in density as the lattice size increased. Although the relative densities differed considerably, both lattices exhibited similar microstructural features such as columnar grains, melt pool boundaries, and surface-attached partially melted powders. No distinct thermal influence was observed with varying unit cell size, demonstrating that uniform build quality was maintained regardless of geometric scale under the given LPBF conditions. Compressive testing revealed that BCC 2 exhibited substantially higher compressive strength (58.47±3.23 MPa) than BCC 4 (1.78±0.11 MPa), which was attributed to enhanced structural stability and a higher number of struts and nodes. Digital Image Correlation (DIC) analysis and cross-sectional microstructure observations confirmed that BCC 2 displayed progressive densification and buckling-dominated deformation, while BCC 4 predominantly exhibited bending-dominated failure with localized deformation. Notably, despite the narrower strut spacing in BCC 2, no discernible thermal influence―such as melt pool distortion or grain coarsening―was identified, indicating that the effect of unit cell size on thermal behavior during LPBF processing remained negligible under the given conditions. These findings were discussed in terms of the effects of lattice unit cell size on microstructure, compressive properties, and deformation behavior. (Received 15 July, 2025; Accepted 19 August, 2025)